Automated Control System For Tomato Plantation - Sulaiman, Siti Fatimah; Ramachandran, Kalaivani (2014)
This project is designed with the aim to facilitate the farmer or gardener to engage in greenhouse systems and improve agricultural technology. The main focus of this project is planting tomatoes and at the same time to promote the cultivation of cold climates plants, especially in Malaysia. Basically, the project consists of two parts; development of program code and mechanical design (prototype). The system will operate only when the input (rain detector, temperature sensors, and humidity sensors) is triggered. The maximum temperature specified for planting tomatoes in this project is 21°C while the minimum soil moisture was 25%RH. This means that if the current temperature reading is below 21°C, the cooling system will stop cooling the greenhouse and if the humidity range is above 25%RH, then the water pump will stop channeling water into the soil. In addition, the system designed is also equipped with indicators that serve to determine either bright or dark surroundings. When it rains, the system will shut the tomato plantation farm by pulling the transparent roof automatically. The purpose of this is to control the water level inside the greenhouse and thus prevent rain from destroying the tomato plants. The entire system is controlled by using Programmable Integrated Circuit (PIC) technology.